Risks and Chances of the Digital Economy in Russia - M. A. Eskindarov; V. V. Maslennikov; O. V. Maslennikov (Финансы: теория и практика)
The study object is the digital economy. The aim of the article is to identify the risks and chances that accompany the rapidly developing digital technologies and penetrate into almost all spheres of human life and society. The following risks were defined: dependence of economic agents on the Internet; displacement of human labor by machinery; backlog of education system from the needs of the digital economy; digital inequality; oligopolization in the information market; reduction of state control over the digital economy; companies gaining significant advantages over consumers due to the use of modern technologies for big data analysis; supranational nature of the digital economy and formation of network global market for goods and services; reduced scope of protectionist measures for national producers and import substitution; rise in cybercrime. The chances are: emerging new professions affected by digitalization; development of security and risk management technologies; automation of industry and provision of services; development of 3D printing and other additive manufacturing technologies; development of end-to-end virtual environment technologies; virtually endless segmentation and restructuring of the digital economy due to permanent appearing and disappearing of its elements (niches); reducing transaction costs; improving the quality of state electronic services for both business and public.